Potensi Ekonomi Rencana Kawasan Transmigrasi Long Apari Kabupaten Mahakam Ulu Kalimantan Timur - Dirgahayu Erri; Hasta Herlan Asymar (Ecoplan, 2021)
In planning the development of transmigration areas, it is necessary to efficiently and effectively realize the development of transmigration areas. The planning process is excellent and correct, and the implementation of the Transmigration Regional Plan (RKT) is agreed upon by all stakeholders both in the center and the region. Transmigration development is one of the efforts to accelerate growth, especially outside Java, to increase its role as a driver of regional development and improve regional competitiveness that is still low. Planning of transmigration settlement areas is carried out with a participatory approach intended for the local community around to act as a subject instead of an object in the planning process of the development of the Transmigration Development Area (WPT) and the Location of Transmigration Settlements (LPT). This is done because they have a direct relationship and interests with the development of settlements transmigration to the economy, management of natural resources, human resources, and the environment. The analysis work is intended to examine the carrying capacity and capacity of the land of the planning site as an agricultural production system and natural resource management that has functional and hierarchical interrelationships with the growth center in a single development system. The preparation of the economic potential of The Transmigration Regional Plan in Long Apari District is done by collecting primary data and secondary data based on the dominant types of commodity cultivation, among others: crops, plantations, industrial plantation forests. The existing economic potential is then implemented in the Determination of Transmigration Business Patterns that also consider investor interest in commodities to be developed in the concession area to improve the regional economy of the Long Apari Transmigration Area Plan.